Characterisation of cosmetic creams prepared by hot mixing technique and cold mixing technique / Nur Amirah M. Bakri - M. Bakri, Nur Amirah (2013)
Mixing process is one of the most important steps in formulating creams or emulsions. Creams were formulated using hot mixing technique and cold mixing technique. Hot mixing technique involves incorporation of heat while cold mixing not. These two mixing techniques were subjected to two formulations of creams. Emulsifiers used in frrst formulation include Olivero and Oliwax while NOVEMER EC-2 polymer was used in second formulation. Both types of creams were then subjected to some tests to compare their physical characteristics. Stability of creams were tested using Lumifuge Stability Analyser to determine the shelf life. Rheology of creams was tested using PHYSICA MCR Rheometer using osscilatory frequency sweep test and shear stress test. Droplets size and uniformity was tested using Malvern Mastersizer. Last but not least, texture of the creams also being analysed using TX-AT Texture Analyser using back-extrusion method. Cold mixing technique was found to give good stability and droplet size with NOVEMER EC-2 emulsifier, better elasticity and texture with or without NOVEMER EC-2 polymer. Besides, cold mixing was found that it is not time consuming and energy safe.